If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(7x + 4) = 2x + -40 Reorder the terms: 8x + -1(4 + 7x) = 2x + -40 8x + (4 * -1 + 7x * -1) = 2x + -40 8x + (-4 + -7x) = 2x + -40 Reorder the terms: -4 + 8x + -7x = 2x + -40 Combine like terms: 8x + -7x = 1x -4 + 1x = 2x + -40 Reorder the terms: -4 + 1x = -40 + 2x Solving -4 + 1x = -40 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 1x + -2x = -40 + 2x + -2x Combine like terms: 1x + -2x = -1x -4 + -1x = -40 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + -1x = -40 + 0 -4 + -1x = -40 Add '4' to each side of the equation. -4 + 4 + -1x = -40 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -40 + 4 -1x = -40 + 4 Combine like terms: -40 + 4 = -36 -1x = -36 Divide each side by '-1'. x = 36 Simplifying x = 36
| 012(y-2)+0.14=0.06-0.03(30) | | (8a^2-22a-21)/(4a+3) | | 4/(x+1)-1/x=1 | | 10+9=5w | | x=log(x+57) | | 676-474= | | 676-404= | | 13.7x+16.3y=147.4 | | x/15=450 | | 305+169= | | 32x^3-12x^2-12x+5=0 | | x+9=y^2 | | 2-5=-7 | | 2(169)-33= | | 5x+3(x+7)=-15 | | 169.75+202.75+306.75= | | -60=-17/2(x-20) | | x^3-14x-12=0 | | 2(169.75)-33= | | 3.9=1.3y | | 3/5x+9/5=7/5x | | 2(170)-33= | | 15c^2-22cd-5d^2= | | a^4-144=0 | | -8+4y+7= | | 6y-7+11y-y+2= | | (3/5)x+(9/5)=(7/5)x | | 4x-9=16-x | | Z=-7/10 | | 8x-(5X+6)=4X-23 | | 6r^3+10r^2-24r= | | x^2+y^2-12x-y=0 |